The evolution & transformation of Baju Kurung in the peninsular of Malaysia / Asliza Aris - Aris, Asliza (Institute of Graduate Studies, UiTM, 2014)
Baju Kurung has existed over more than 600 years ago. It has been the pride and heritage of the Malay society since the Great Malaccan Sultanate in the 15th Century. Since then, Baju Kurung has gone through some changes, which include its length, cut and shape, fabrics, style and coordination. Baju Kurung name is well- known to Malaysian society especially to the Malay people. It is common that any garment that resemblance the form of Baju Kurung is often called Baju Kurung (Moden). Due to this assumption, this research tends to construct an understanding that draws the line between traditional Baju Kurung and Baju Kurung Moden.